2016
DOI: 10.1016/j.zool.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Balancing selection on immunity genes: review of the current literature and new analysis in Drosophila melanogaster

Abstract: Balancing selection has been widely assumed to be an important evolutionary force, yet even today little is known about its abundance and its impact on the patterns of genetic diversity. Several studies have shown examples of balancing selection in humans, plants or parasites, and many genes under balancing selection are involved in immunity. It has been proposed that host-parasite coevolution is one of the main forces driving immune genes to evolve under balancing selection. In this paper, we review the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 105 publications
2
37
0
Order By: Relevance
“…Moreover, in the studies [36] and [37], the authors look for balancing selection only in a small part of the genome of D. melanogaster . We also find little overlap when we compare the results to our earlier study [8]: only one gene ( CG18208 ) is shared for the African candidate genes. This discrepancy might again be explained by our different methodology and different dataset.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Moreover, in the studies [36] and [37], the authors look for balancing selection only in a small part of the genome of D. melanogaster . We also find little overlap when we compare the results to our earlier study [8]: only one gene ( CG18208 ) is shared for the African candidate genes. This discrepancy might again be explained by our different methodology and different dataset.…”
Section: Discussionmentioning
confidence: 52%
“…Unckless et al [36] found evidence of alleles maintained by balancing selection in genes encoding antimicrobial peptides. Nonetheless, examples of genes under balancing selection in D. melanogaster are still scarce, and no genome-wide analysis for balancing selection has been done in this species with the exception of our own previous preliminary work [8]. Based on the availability of a wealth of NGS data we approached the difficulties of detecting balancing selection in the genome using two common statistics (high genetic diversity and intermediate-frequency polymorphism), without specifying a certain type of balancing selection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations